Linhas de transmissão de energia elétrica: estudo sobre compatibilidade eletromagnética - Silva, Hugo Manoel Oliveira da (2012)
This work presents a study on transmission lines in the Brazilian electric sector, focusing on the issue of human exposure to electric and magnetic fields generated by these facilities, highlighting regulatory and technical issues and measurements of these fields, as well as compatibility with emissions limits established by national legislation. To achieve this goal are described the principles of electromagnetism, as well as the mathematical models that describe this phenomenon. Specifically, is also presented a mathematical model for calculating electric and magnetic fields generated by transmission lines of electricity to ensure a reliable result. In its final part is a revision of the Brazilian legislation on the subject, and presents some results of measurements of electric and magnetic fields emitted by power lines, as well as simulations using the computer program.